Roles of Fatty Acid Chain Length and Enzyme-Oriented Drug Controlled Release from pH-Triggering Self-Assembled Fatty Acid Conjugated Quetiapine Nanosuspensions - Nguyen, Hy D.; Ngo, Hai V.; Nguyen, Van Hong; Gil, Myung Chul; Lee, Beom Jin (International Journal of Nanomedicine, 2023)
Background: Quetiapine (QTP) is a first-line antipsychotic drug, but its therapeutic druggability and patient adherence were limited due to high oral dose strength, low bioavailability and physicochemical/biopharmaceutical issues. Purpose: To investigate the roles of fatty acid chain length and enzyme-oriented QTP controlled release from pH-triggering self-assembled fatty acid conjugated QTP nanosuspensions (NSPs). Methods: QTP was conjugated with different chain length fatty acids (C10–decanoic acid, C14–myristic acid, C18–stearic acid) to obtain QTP-fatty acid conjugates (QFCs: QD, QM, QS) by exploiting 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide/4-dimethylaminopyridine (EDC/DMAP) conjugation chemistry. Then, the solubility, partitioning coefficient (log P), cell viability and cleavage kinetics of QFCs were evaluated. The pH-triggering self-assembled behaviors of QFCs to form QTP-fatty acid NSPs (QDN, QMN, QSN) by varying pH, QFC concentration and proton-to-QTP ratios were characterized. The morphological images, critical micelle concentration (CMC), physico-chemical properties and enzyme-oriented QTP controlled release of NSPs were examined. Results: Three QFCs were synthesized with different chain length fatty acids from QTP after desalting fumarate from QTP fumarate. The pH, QFC concentration and proton-to-quetiapine molar ratio could influence physicochemical properties and nanonization behaviors of QFCs. All three QFCs showed no effect on the viability of myoblast cells. The pH-triggering self-assembly of amphiphilic QFCs to form nanoparticles (NPs) occurred as the amine moiety of QTP was readily ionized in a strongly acidic environment (pH 1.2). Interestingly, the longer the fatty acid chain length, the lower water solubility, the higher log P (lipophilicity) and the smaller NP particle size were observed. The conversion rate of QFCs to liberate QTP by esterase in human plasma and liver S9 fractions was also inversely proportional to the fatty acid carbon chain length. Interestingly, the freeze-dried QMN showed the esterase-oriented controlled release of QTP over one month, unlike the initial burst release of QDN or the slowly delayed release pattern of QSN. Conclusion: A new pH-triggering self-assembled nanonization platform was developed using different chain length fatty acid conjugated QTP in low pH environment. By varying fatty acid chain length, the enzyme-oriented QTP controlled release dosage form was challenged to enhance the therapeutic effectiveness of QTP.
Keywords: Delayed-Action Preparations; Esterases; Fatty Acids; Fumarates; Humans; Hydrogen-Ion Concentration; Protons; Quetiapine Fumarate; enzyme-oriented controlled release; fattigation platform; fatty acid chain length; fatty acid conjugated quetiapine; nanonization; nanosuspension; pH-triggering self-assembly; quetiapine